Analysis of the impact of social insurance on farmers in China: A study exploring subjective perceptions of well-being and the mechanisms of common prosperity - Cheng, Yongsheng; Zhang, Deyuan (Frontiers in Psychology, 2022)
It has been more than 10 years since the implementation of the new rural social pension insurance (hereinafter referred to as "new rural insurance、NPS"), and the policy effects have gradually emerged. To study the impact of NPS on the subjective well-being of its direct beneficiaries, it is helpful to better understand and summarize the implementation performance of NPS and promote the sustainable development of the rural social pension system. Based on the latest CFPS data, the Order Proboit model was used to analyze in depth the impact of rural residents' insurance participation behavior on subjective well-being, to identify the possible different effects of different age groups, gender, and regions on farmers' subjective well-being, and to test the mediating effects of health status and self-rated social status on farmers' subjective well-being and their mechanisms of action. The study found that the act of participating in insurance can significantly improve the subjective well-being of rural residents, but there are also heterogeneous characteristics, and the biggest beneficiaries of NPS are rural residents with poor health status and good overall conditions. Accordingly, it is proposed to implement social old-age security policies according to local conditions, pay more attention to the social identity and health status of rural residents, and gradually realize the equalization of basic public services between urban and rural areas and between regions.